Tax Planning and Firm Value: Evidence from Malaysia - Mohd Razali, Mohd Waliuddin; Siti Shahfina, Ghazali; Janifer, Lunyai; Tan, Josephine Hwang Yau (2018)
The main objective of this study is to determine the impact of tax planning on firm value of firms listed in Bursa Malaysia. Tax planning proxies in this study are the Effective Tax Rate(ETR)and Book Tax Differences (BTDs). The 387 samples data were collected from the Data Stream from period of2014 to 2016. After controlling the firm size, leverage, asset tangibility, firm age and dividend, the regression results show that ETR hasa significant and positive relationship with firm value while BTDs has insignificant negative relationship with firm value. Firm withless tax planning activities may signal investors that the firm is more transparent in publishing their financial information. Most of our control variables such as leverage, asset tangibility, firm age and dividend have negative relationship with firm value. This study suggests that ETR proxy is suitable to determine firm value rather than BTDs. For future research, this study can be expanded by using more sample size from a longer time frame of research.